2010
DOI: 10.1007/s11270-010-0694-4
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric Absorption of Fluoride by Cultivated Species. Leaf Structural Changes and Plant Growth

Abstract: Fluoride (F) is an air pollutant that causes phytotoxicity. Besides the importance of this, losses of agricultural crops in the vicinity of F polluting industries in Brazil have been recently reported. Injuries caused to plant leaf cell structures by excess F are not well characterized. However, this may contribute to understanding the ways in which plant physiological and biochemical processes are altered. A study evaluated the effects of the atmospheric F on leaf characteristics and growth of young trees of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 30 publications
0
12
0
2
Order By: Relevance
“…Contudo, Mesquita et al (2011) verificaram pequenas alterações anatômicas na ausência de danos visuais, principalmente a ocorrência de perda no contorno das paredes celulares, além da retração do parênquima lacunoso quando esta espécie foi submetida à contaminação pelo F.…”
Section: Concentração De Flúor Nas Folhas E Sintomas Visuais Da Toxicunclassified
“…Contudo, Mesquita et al (2011) verificaram pequenas alterações anatômicas na ausência de danos visuais, principalmente a ocorrência de perda no contorno das paredes celulares, além da retração do parênquima lacunoso quando esta espécie foi submetida à contaminação pelo F.…”
Section: Concentração De Flúor Nas Folhas E Sintomas Visuais Da Toxicunclassified
“…The alterations in the epicuticular layer may compromise the survival of plant species, as the epicuticular layer is the first defensive wall against the environmental stress (PAL et al, 2002). The structure of the epicuticular wax are epidermic parameters and are related to differences in plant susceptibility or resistance to pollution (NEINHUIS; BARTHLOTT, 1998), being that micromorphology is a promising biomarker on the evaluation of stresses caused by atmospheric pollutants (SILVA et al 2005;SANT'ANNA-SANTOS et al, 2006a,b).…”
Section: Discussionmentioning
confidence: 99%
“…The deposition of particulate matter on the leaf surface causes blockage of solar radiation by shadowing the leaf surface, altering the pigment synthesis, and the photosynthetic rate (HIRANO et al, 1995;NAIDOO;CHIRKOOT, 2004;OLIVEIRA et al, 2007;KUKI et al, 2008b;PEREIRA et al, 2009). Additionally, the obstruction of the stoma may cause the increase of the leaf temperature, the alteration of the transpiratory rate (PEREIRA et al, 2009) and anatomical and ultrastructural modifications in leaf tissues organization (SILVA et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One experiment conducted by Mesquita et al [38], reported that damage to the epidermis and stomata of leaves from young plants of coffee and orange when these are exposed to Fluoride accumulation also hampered the photosynthesis.…”
Section: Effects Of Fl Uoride On Photosynthesismentioning
confidence: 99%